Geopolitical turmoil and energy dynamics: Analyzing the impact on inflation in selected European economies - Cumali Marangoz (Heliyon)
This paper attempts to examine the impact of energy price shocks, monetary policy, and geopolitical events on inflation in selected European countries across different periods of time by applying a Time-Varying Parameter Vector Autoregressive (TVP-VAR) model with stochastic volatility. The analysis displays the diverse impact of gas prices on the Consumer Price Index (CPI), a gauge for inflation, in the short, medium, and long term. Moreover, the findings show that oil price shocks with deflationary trends during COVID-19 have inflationary consequences. The results also show that the European Central Bank's response to the pandemic-induced economic downturn has affected long-term inflation trends. Furthermore, significant geopolitical risks that arose from the Russia-Ukraine war amplified inflationary trends. The findings contribute valuable insights into the multifaceted dynamics shaping inflation in European economies.